Strain-induced modulation of electronic, optical, and transport properties in PtX2 (X=S, Se) monolayers - Gonzalo, Fredy Mamani; Rivera, Victor José Ramirez; Piotrowski, Maurício Jeomar; Laura, Gohnny Acero [UNESP]; Simoes, A. Z. [UNESP]; Flores, Efracio Mamani (Elsevier, 2025)
We investigate the structural, electronic, optical, and transport properties of PtS2 and PtSe2 monolayers under biaxial strain. Both materials exhibit a transition to a quasi-direct bandgap, with PtS2 and PtSe2 showing quasi-direct bandgaps of 0.78 eV (PBE) and 1.22 eV (HSE06), and 1.10 eV (PBE) and 1.73 eV (HSE06), respectively. Optically, PtS2 demonstrates a strong absorption coefficient of 81.42 × 104 cm−1 at ɛ = −8%. In terms of thermal properties, the lattice thermal conductivity (κl) decreases under tensile strains, reaching 4.13 W m−1 K−1 at +8% for PtS2, while PtSe2 shows a minimum value of 2.61 W m−1 K−1 at +8% strain at 800 K. These results highlight the tunable electronic, optical, and thermal properties of PtS2 and PtSe2, positioning them as promising candidates for optoelectronic and thermoelectric applications
Keywords: Biaxial strain; DFT; Monolayer; Optical properties; Phonon transport